2012
DOI: 10.1016/j.cub.2012.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Pez Acts in Hippo Signaling to Restrict Intestinal Stem Cell Proliferation

Abstract: The conserved Hippo signaling pathway acts in growth control and is fundamental to animal development and oncogenesis. Hippo signaling has also been implicated in adult midgut homeostasis in Drosophila. Regulated divisions of intestinal stem cells (ISCs), giving rise to an ISC and an enteroblast (EB) that differentiates into an enterocyte (EC) or an enteroendocrine (EE) cell, enable rapid tissue turnover in response to intestinal stress. The damage-related increase in ISC proliferation requires deactivation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
97
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(103 citation statements)
references
References 58 publications
6
97
0
Order By: Relevance
“…[37][38][39][40][41][42] It was found that cytoplasmic PTPN14 inhibits oncogenic activity of YAP by binding and sequestering it from the nucleus. Interestingly, PTPN14 translocation to the nucleus is associated with induction of proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39][40][41][42] It was found that cytoplasmic PTPN14 inhibits oncogenic activity of YAP by binding and sequestering it from the nucleus. Interestingly, PTPN14 translocation to the nucleus is associated with induction of proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Drosophila Pez is a newly identified component of the Hippo signalling pathway and specifically functions to restrict the growth of adult midgut epithelium 16 . To date, the degradation mechanism of Pez remains poorly defined.…”
Section: Su(dx) Governs Pez Stability Against Proteasomal Degradationmentioning
confidence: 99%
“…We used a functional GFP-tagged Pez (Pez-GFP), which is encoded by a genomic rescue construct, to indicate the endogenous Pez protein levels (Fig. 1d) 16 . Pez RNAi transgene (v40743) was expressed under the control of the patched-Gal4 (Ptc-Gal4) driver, which drives gene expression in a stripe of anterior compartment cells along the anterior/posterior (A/P) compartment boundary of imaginal discs.…”
Section: Su(dx) Governs Pez Stability Against Proteasomal Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…Double mutations of these genes produce phenotypes closely resembling those caused by mutations of Hippo pathway components. In addition, Pez may activate the Hippo pathway by binding to Kibra (Poernbacher et al, 2012). The Fat protocadherin, a cell surface molecule, was also identified as an upstream regulator of the Hippo pathway (Bennett and Harvey, 2006;Cho et al, 2006;Silva et al, 2006;Willecke et al, 2006;Tyler and Baker, 2007).…”
Section: The Drosophila Hippo Pathwaymentioning
confidence: 99%